HYBRID MODEL OF RSA, AES AND BLOWFISH TO ENHANCE CLOUD SECURITY - Kaur, Jasleen; Bagga, Sachin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Cloud is a term used as a metaphor for the wide area networks (like internet) or any such large networked environment. It came partly from the cloud-like symbol used to represent the complexities of the networks in the schematic diagrams. It represents all the complexities of the network which may include everything from cables, routers, servers, data centers and all such other devices. Cloud based systems saves data off multiple organizations on shared hardware systems. Data segregation is done by encrypting data of users, but encryption is not complete solution. We can do segregate data by creating virtual partitions of data for saving and allowing user to access data in his partition only. In our research work we have used the hybrid combination of RSA, AES and Blowfish for data encryption along with data fragmentation using Gateway.